The epidemiology and management of odontogenic keratocysts (OKCs): A European multicenter study. Issue 1 (January 2022) - Boffano, Paolo; Cavarra, Francesco; Agnone, Anna Maria; Brucoli, Matteo; Ruslin, Muhammad; Forouzanfar, Tymour; Ridwan-Pramana, Angela; Rodríguez-Santamarta, Tanía; de Vicente, Juan Carlos; Starch-Jensen, Thomas; Pechalova, Petia; Pavlov, Nikolai; et al.
Abstract: The objective of the present study was to assess the epidemiology including demographic variables, diagnostic features, and the management of odontogenic keratocyst (OKCs) at several European departments of maxillofacial and oral surgery. This study is based on a systematic computer-assisted database that allowed the recording of data from treated OKCs. The following data were recorded for each patient: gender, age, voluptuary habits, comorbidities, site, size, radiographic features, treatment of OKCs, length of hospital stay, complications, recurrence, management and complications of eventual recurrence. A total of 405 patients, 249 male and 156 female, with 415 OKCs (407 sporadic and 8 syndromic lesions) were included in the study: 320 lesions were found in the mandible, whereas 95 were found in the maxilla. In the mandible, the most frequently involved subsite was the angle, whereas in the maxilla it was the molar region. The most frequently performed treatment option was enucleation plus curettage/peripheral ostectomy in 204 OKCs (recurrence rate, 9%). Decompression without residual cystectomy (recurrence rate, 66%), marsupialization with residual enucleation with the use of Carnoy's solution (recurrence rate, 50%), decompression with residual cystectomy (recurrence rate, 43%), and simple enucleation (recurrence rate, 24%) were the treatment options with the highest recurrence rates. An appropriate management of odontogenic keratocysts should be individualized, taking into consideration clinical and radiological findings, as well as patients' age and comorbidities.